Penegakan Hukum Terhadap Pungutan Liar yang dilakukan oleh Pos Polisi kepada Pengendara Angkutan Barang di Wilayah Kepenghuluan Bangko Bakti Kecamatan Bangko Pusako Kabupaten Rokan Hilir - Padri, Muhammad; Edorita, Widia; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Wild charges against law enforcement carried out by the police to transport riders relic items Kepenghuluan Bangko Bangko, sub episode of filial piety, Rokan Hilir. charges made by the police station diKepenghuluan Bangko Bakti done with work shift system activity is certainly contrary to law No. 20 of 2001 about the eradication of criminal acts of corruption in article 12 the letter e that reads, are convicted with imprisonment for life or imprisonment of most short four (4) years old and most 20 (twenty) years and criminal fines of at least Rp. 200,000,000.00 (two hundred million rupiah) and at most Rp. 1,000,000,000.00 (one billion rupiah) . Tujujan penilitian these are: a. to know wild charges against law enforcement carried out by the Police to transport goods b. riders to know the constraints in the wild charges against law enforcement by the Police to transport the goods c. Rider To attempt countermeasures so that goods transport riders do not become victims of the wild collection.The type of research or the approach used by the author is the juridical sociological legal research. This research was conducted in the area of Kepenghuluan Bangko Bangko, sub episode of filial piety, Rokan Hilir. As for the reason the author sets the location became the site of the author's research because of indications of wild charges committed by police against rider transport of goods in the region. In this study researchers use data sources that you can break down as follows: primary Data, i.e. data obtained directly provide research. Secondary data, i.e. data obtained indirectly through the research libraries (library research).The issue of the proper functioning of the law in principle hold at least four factors, namely: the ruling factor, factor officers who enforce, support facilities, and the citizens of the community. As for the barriers in law enforcement is the mental attitude of the person's own officers, the lack of legal consciousness of the person doing the pungli and feel good will his deeds led to constraints in enforcing law, victims do not want to report the actions of the members of the police who did the wild charges. And as for the efforts of the response is: Identify areas that could potentially occur wild charges and take effective measures to eradicate wild charges, forcefully crack down on the country's civil apparatus involved wild charges, conduct more in-depth investigation to trawl the involvement of other persons-personsKeywords: wild charges against law enforcement in Kepenghuluan Bangko Bakti